Theory and empirical evidence of the gender wage gap - Ali, Hassan; Othman, Noraini; Zakaria, Nazlina (Penerbit Universiti Utara Malaysia, 2008)
Women participation in the labour force has steadily increased over the last several decades.Despite this, women still remain in lower status, less interesting and less and less well paid jobs.Differences in family and economic roles between men and women have resulted in wage discrimination between men and women.Attempts to explain the gender wage differential generally rely on human capital and labour market segmentation theories.The human capital theory attributes wage differentials to differences in education, training, and work experience. Labour market segmentation theory on the other hand attributes wage differentials to the segmentation of the labour market into primary and secondary sectors.The human capital theory remains the dominant theory explaining wage differentials between males and females. Research evidence does suggest that differences in the level of education and experience between male and female influence wages.